Metode Pengembalaan melalui Pendekatan Lintas Budaya - Sinaga, Janes; Simanjuntak, Rimon Jonas; Sinambela, Juita Lusiana (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Abstract: The purpose of this research is that every pastor pays attention to how to approach members of his congregation, especially a cross-cultural approach, so that it is easier to provide the best service if you are familiar with the culture of the congregation being served. Each region has a different culture. And a minister of God or pastor in ministry is often placed in a place that is different from its culture and customs. For success in the ministry of a Pastor it is necessary to study and understand the local culture and customs. This approach through cultural understanding will make it easier for God's ministers to win the hearts of the local population and adapt the preaching of the gospel to the culture of the local community. The approach through understanding the local culture as well as the local language, makes it easier to communicate the truth of God's word. This study uses a qualitative method that describes the importance of a cross-cultural approach in pastoral care, with the hope that the service will be more pleasing to the members it serves.Abstrak: Tujuan Penelitian ini adalah agar setiap gembala memperhatikan cara pendekatan kepada anggota jemaatnya, terutama pendekatan lintas budaya, sehingga lebih mudah untuk memberikan pelayanan yang terbaik apabila mengenal dengan baik budaya jemaat yang dilayani. Setiap daerah memiliki budaya yang berbeda-beda. Dan seorang pelayan Tuhan atau pendeta dalam pelayanan sering ditempatkan di suatu tempat yang berbeda dengan budaya dan adat istiadatnya. Untuk keberhasilan dalam pelayanan seorang Pendeta adalah perlu untuk mempelajari serta memahami budaya serta adat istiadat setempat. Pendekatan melalui pemahaman budaya ini akan memudahkan para pelayan Tuhan untuk memenangkan hati penduduk setempat serta menyesuaikan pengabaran Injil dengan budaya masyarakat setempat. Pendekatan melalui pemahaman budaya lokal dan juga bahasa lokal, memudahkan untuk mengkomunikasikan kebenaran firman Tuhan. Penelitian ini menggunakan metode kualitatif yang memaparkan pentingnya pendekatan lintas budaya dalam pelayanan penggembalaan, sehingga tercipta sebuah pelayanan yang berkenan kepada anggota yang dilayaninya.